#### Answer

$0$

#### Work Step by Step

$=24\div4[2-(5-2)]^{2}-6$
$=24\div4[2-(3)]^{2}-6$
$=24\div4[-1]^{2}-6$
$=24\div4-6$
$=6-6$
$=0$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$0$

$=24\div4[2-(5-2)]^{2}-6$
$=24\div4[2-(3)]^{2}-6$
$=24\div4[-1]^{2}-6$
$=24\div4-6$
$=6-6$
$=0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.